Inventory Management Model for Reducing Stockout rate by Applying Lean Warehousing and DDMRP Tools in a SMEs in the Commercial Sector - Salcedo Portocarrero, Nezari Paloma (2023)
In Peru, commercial SMEs currently represent 35% of the total, showing an average annual growth of 3.3%. However, they are facing increasing challenges in logistics management due to the growth in demand and deficiencies in the supply chain as a result of the international situation. This case study addresses the problem of stock-outs and purchase planning, which represent the greatest impact on the economic loss for the company studied. For these, the implementation of the 5S methodology is proposed hand in hand with the Visual Management in order to have a better control of the stock and improve the work flow, in addition, the purchase planning is proposed from the application of the DDMRP tool with the objective of being able to meet the demand and have lower losses due to expiration of products. For the analysis of the problem and the proposal approach, a focus was made on the main products sold, the Value Stream Mapping tool was used for the process analysis and the analysis of the main causes by means of Pareto diagrams and the Systematic Interrogation Technique. Finally, through the application and simulation of the proposed tools, an average reduction of 28.3% in warehouse ordering times and 25% in order preparation times is evidenced, likewise the DDMRP tool shows a reduction of stock breakage, managing to cover 100% of the demand.